The effect of NLRP3 inflammasome on cardiovascular prognosis in patients with acute coronary syndrome - De-Gang Mo; Ming-Ting Liang; Li Xu; Tai Li; Qian-Feng Han; Chen Chen; Heng-Chen Yao (Scientific Reports)
Abstract The NOD‑like receptor protein domain associated protein 3 (NLRP3) inflammasome is critical in inflammatory responses and may be a valuable prognostic biomarker in acute coronary syndrome (ACS). We aimed to investigate the association between NLRP3 inflammasome levels and short-term outcomes in patients with ACS. We enrolled 295 patients with ACS who were monitored for 6 months for major adverse cardiovascular events (MACEs). The NLRP3 inflammasome was quantified using enzyme-linked immunosorbent assays, with the Gensini score used to assess disease severity. A Cox regression model evaluated whether NLRP3 inflammasome levels were independent predictors of MACEs. Spearman correlation analysis demonstrated a significant positive correlation between NLRP3 inflammasome levels and the Gensini score (r = 0.55, p < 0.001). Plasma NLRP3 inflammasome levels were significantly higher in the MACEs group (8.48 ng/mL) compared with the no-MACEs group (3.48 ng/mL) (p < 0.001). Multivariate Cox regression identified NLRP3 inflammasome content as an independent risk factor for MACEs (hazard ratio 1.104, p = 0.001; area under the curve: 0.780 [95% confidence interval 0.721–0.840], p < 0.001). Elevated plasma NLRP3 inflammasome levels correlated with ACS severity and were associated with poorer short-term outcomes in patients with ACS.